2018
DOI: 10.1177/1071100718816052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Type of Fixation of Akin Osteotomy

Abstract: Background: The objective of the study was to assess the influence of the type of fixation of the Akin osteotomy when used during hallux valgus surgery. Methods: Between 2013 and 2016, we performed 138 Akin osteotomy procedures employing a staple (group A, 43 patients), screw (group B, 47 patients), and single or double transosseous suture stabilization (group C, 48 patients). We assessed the pre- and postoperative interphalangeal angle (IPA), hallux valgus angle (HVA), and intermetatarsal angle (IMA) on dorso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 27 publications
0
20
0
7
Order By: Relevance
“…The need of material removal as a minor complication after Akin osteotomy is reported in 1.5- 10 %. 6,8,18 Our study found a relatively high risk of material conflict, as 13 screws (15.1%) had to be removed because of soft tissue irritation in OS group.…”
Section: Discussionmentioning
confidence: 65%
“…The need of material removal as a minor complication after Akin osteotomy is reported in 1.5- 10 %. 6,8,18 Our study found a relatively high risk of material conflict, as 13 screws (15.1%) had to be removed because of soft tissue irritation in OS group.…”
Section: Discussionmentioning
confidence: 65%
“…18,23,40 The literature presents reports describing very good results of the Akin osteotomy fixation performed as an open procedure using a single- or double-channel transosseous suture. 10,25,29,36,38,39…”
Section: Discussionmentioning
confidence: 99%
“…18,23,40 The literature presents reports describing very good results of the Akin osteotomy fixation performed as an open procedure using a single-or double-channel transosseous suture. 10,25,29,36,38,39 The first author of the present study has developed a method of fixation employed in the Akin osteotomy of the proximal phalanx of the big toe by means of the percutaneous transosseous suture (ie, PTSA). Similarly, like open procedures, such an approach allows for reducing the costs of surgery and the risk of complications associated with using a screw, such as soft tissue irritation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations